2021
DOI: 10.2478/forj-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of game browsing on natural regeneration of European beech (Fagus sylvatica L.) forests in the Krušné hory Mts. (Czech Republic and Germany)

Abstract: Tree damage by game browsing is one of the biggest threats to forest ecosystems at the time of climate change and large-scale forest disturbances. The aim of the paper was to determine the effect of browsing by ungulates on the diversity, abundance and species composition of natural regeneration in forest stands dominated by European beech (Fagus sylvatica L.). The research was conducted on 10 permanent research plots in the Krušné hory Mts. in the Czech Republic and Germany. The density of natural regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 100 publications
(70 reference statements)
2
2
0
Order By: Relevance
“…Our findings and those reported in other studies [ 20 , 21 , 43 ] suggested that presence of softwood broadleaved species can act as biological control against LWH browsing on economical tree species. Therefore, we recommend that these softwood broadleaved species (except birches in Central Europe) be retained within vulnerable forest stands during cleanings, thinning and tending.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings and those reported in other studies [ 20 , 21 , 43 ] suggested that presence of softwood broadleaved species can act as biological control against LWH browsing on economical tree species. Therefore, we recommend that these softwood broadleaved species (except birches in Central Europe) be retained within vulnerable forest stands during cleanings, thinning and tending.…”
Section: Discussionsupporting
confidence: 87%
“…Although they prefer grasses, a substantial amount of their diet, especially in winter, is also composed of foliage, branches, and the bark of trees and woody shrubs [ 17 , 18 ]. To maximize their intake of digestible energy and protein, red deer select the most nutritious plant species and plant parts with sufficient abundance that are available [ 19 , 20 , 21 ]. However, when population density is high, intraspecific competition forces animals to also consume lower quality forages [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that Sorbus aucuparia L. and Betula pendula Roth are highlight species, Fagus sylvatica L. and Picea abies broad species, and Quercus a nowhere species. The ranking of the species is consistent with the group definitions for browsing sensitivity [6,10,25,35,42,[73][74][75], shade tolerance [23,76], and how their growth is affected by light conditions (Figure S8). When canopy cover is low, birch and Sorbus aucuparia L. grow faster than other species, and ungulate pressure reduction can strongly increase their recruitment, in contrast to Quercus, which grows slowly and whose development is strongly affected by other competing species.…”
Section: How Browsing Alters Seedling Competition and Likely Recruitm...supporting
confidence: 74%
“…On the one hand, however, the speed of active forest conversion is currently not keeping pace with the dying of forest stands. On the other hand, a lack of mother trees for deciduous trees and Abies as well as excessive game populations slow down natural forest change (Fuchs et al, 2021). In the future, Fagus, other deciduous trees, and possibly also Abies in the Erzgebirge will probably benefit from the rising temperatures resulting from climate change and expand upwards.…”
Section: Modern Forest Dynamicsmentioning
confidence: 99%